4D result enhancement with crosscorrelation-based time-lapse static correction at Ketzin, Germany - Bergmann, P.; Kashubin, A.; Ivandic, M.; Lüth, S.; Juhlin, Christopher (EAGE Publishing BV, 2014)
A method for correction of time-lapse differences (TLD) in the statics of seismic data from repeated surveys is presented. Such static differences are typically caused by changes in the near-surface velocities between the acquisition repeats and have a deteriorating impact on the time-lapse image. Trace-to-trace time shifts are determined from the pre-stack data sets using cross-correlations. These time shifts are decomposed in a surface-consistent manner, which is providing a static correction that is capable of aligning the repeat data to the baseline data. The approach is demonstrated on a 4D seismic data set from the Ketzin CO2 pilot storage site, Germany, and is compared with results of an initial processing that was based on individual refraction static corrections. It is shown that the proposed TLD static correction reduces 4D noise more effectively than refraction static corrections while being significantly less labor intensive.